The green-ol (green-alcohol) economy - Lee, Woong Hee; Kim, Kyeongsu; 고재현; 이동기; 원다혜; 오형석; 이웅; 민병권 (Elsevier BV, 2023)
Carbon dioxide (CO2) emissions by burning fossil fuels have contributed to the global warming that has already led to several hazard and disaster risks, further magnified by climate change. Fossil fuel utilization as an energy resource is the main cause of CO2 emission; therefore, a new energy economic concept is required to achieve carbon neutrality to mitigate climate change impacts. Here, we propose a green-alcohol (green-ol) economy wherein green-ol, a major chemical used in CO2 recycling, can serve as fuel for land (e.g. ethanol) and air transport (e.g. butanol), and as a liquid organic hydrogen carrier (LOHC, e.g. methanol) for green hydrogen. The essential and triggering step in the green-ol process is an e-chemical process wherein CO2 is directly electrolyzed by clean net-zero electricity. Moreover, two important technologies, green-ol production from CO2 and dehydrogenation of green-ol, are reviewed and their challenges and limitations are discussed with the aim of building an achievable green-ol economy.